2000
DOI: 10.2337/diabetes.49.12.1998
|View full text |Cite
|
Sign up to set email alerts
|

Suppression and acceleration of autoimmune diabetes by neutralization of endogenous interleukin-12 in NOD mice.

Abstract: A corpus of evidence suggests that T-helper type 1 (Th1)-dependent cellular immunity plays a pivotal role in the pathogenesis of autoimmune diabetes. This study was intended to find ways to prevent the development of NOD diabetes using a neutralizing anti-interleukin (IL)-12 antibody (C17.8) that inhibits Th1 cell differentiation. When C17.8 was administered from 5 to 30 weeks of age, NOD mice exhibited suppression of both insulitis and diabetes. However, when C17.8 administration ceased at 15 weeks of age, 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 59 publications
(61 reference statements)
1
24
0
1
Order By: Relevance
“…The unexpected finding that IL-12 (as well as IFN-␥)-deficient NOD mice do not develop diabetes appears to be due to the time of onset of the blockade in the knockout and development of compensatory regulatory pathways that do not function in intact mice (32)(33)(34). Conversely, a lack of IL-12 would be expected to promote Th2 dominance and the B cell hyperactivity characteristic of lupus.…”
Section: Discussionmentioning
confidence: 96%
“…The unexpected finding that IL-12 (as well as IFN-␥)-deficient NOD mice do not develop diabetes appears to be due to the time of onset of the blockade in the knockout and development of compensatory regulatory pathways that do not function in intact mice (32)(33)(34). Conversely, a lack of IL-12 would be expected to promote Th2 dominance and the B cell hyperactivity characteristic of lupus.…”
Section: Discussionmentioning
confidence: 96%
“…It is therefore interesting that paradoxical results have been obtained when treating NOD mice with either exogenously administered IL-12 or specific IL-12 inhibitors (monoclonal antibody, the (p40)2 antagonist); the outcome apparently depending on the time of administration during the disease development [27][28][29][30][31][32]. More concording data have recently been obtained by use of transgenic mice whose pancreatic cells constitutively express either biologically active IL-12 or the IL-12 p40 homodimer a naturally occurring antagonist of IL-12 [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-IFN-␥ antibodies reduce the incidence of diabetes in both the MLDS-induced model (Herold et al, 1996) and NOD mouse (Campbell et al, 1991); anti-IL-12 antibodies have proved to be effective at suppressing diabetes in the NOD mouse (Fujihira et al, 2000). Antibodies against IL-1 (Cailleau et al, 1997) and TNF-␣ (Yang et al, 1994) have both been shown to prevent diabetes in the NOD mouse.…”
Section: Discussionmentioning
confidence: 99%